Penyuluhan Hipertensi Sebagai Usaha Peningkatan Pengetahuan pada Warga Desa Jayagiri Lembang - Sujana, Treesia; Sianipar, Imelda MG; Sinaga, Anni; Ardayani, Tri; Tresnajaya, Reynaldi; Hariningsih, Wintari (Lembaga Dongan Dosen, 2024)
Hypertension is a significant health problem worldwide, especially in Indonesia, where the prevalence of hypertension increases rapidly every year. Preliminary survey results in Jayagiri Village showed a problem of lack of knowledge and compliance with treatment among the population. Therefore, the Immanuel Institute of Health's community service team is conducting health care activities with the aim of increasing the knowledge of participants about hypertension and its impact. Blood pressure tests of 26 participants showed that 42.3% fall into the category of hypertension. Assessment results show that participants acquired significant knowledge after examination marked by an increase of 38.5% in the number of participants with a good knowledge category. Although Spearman's Rank bivariate test on the initial knowledge variable and blood pressure showed no correlation, increased knowledge is expected to help change towards positive behavior. From the results of this community service, it can be concluded that in achieving ideal blood pressure control, along with health education, additional interventions are needed, such as lifestyle changes and support for in the implementation of hypertension and self-efficacy.